(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
In the article tectonic-geomorphological analyses were done with the aim of tectonic activity observation of blocks of the territory of Armenia. By analyses the most active and passive block units were highlighted. The relations between blocks tectonic activity and seismicity were observed, in the result of which general regularities of confinement of seismic events (with different strength) to certain interblock tectonic situations were revealed. On the bases of block tectonic activity differences the qualitative assessment of seismotectonic potential of fault different segments was done.